Evaluating the effects of subsoiler type and spacing on tillage resistance and soil conservation with DEM simulation and field experiment - Wang, Yueming; Lu, Chenjie; Fan, Jiajun; Zhang, Xu; Chen, Kai; Chen, Jing; Li, Xiaoguang (International Journal of Agricultural and Biological Engineering, 2025)
Multi-subsoiler collaboration plays a significant role in improving the efficiency of subsoiling. High tillage resistance during subsoiling seriously affects consumption, and the excessive soil disturbance may result in an increase in the amount of water that evaporates from the soil, which is unfavorable for water conservation. However, the space arrangement and types of subsoiler are key parameters for design of a set of subsoilers and have a major effect on tillage resistance and soil disturbance, which is a critical performance indicator of subsoiling. In this paper, a set of subsoiler models were developed using DEM. A field experiment was conducted in the sowing season in an experimental field of 1 hm2 with black soil of Juliangtun Village, Liaoning Province. In both the simulation and experiment, six types of subsoilers (TC-SM, TC-SC, TA-SM, TA-SC, TDW-SM, and TDW-SC) were investigated at three different spacing arrangements (500, 600, and 700 mm), a constant vertical distance between the front and back subsoilers (500 mm), a constant working speed (3 km/h), and a constant working depth (400 mm). The mechanism of resistance was analyzed. The results showed that the tillage resistances of the six types of subsoilers were in the descending order of FTDW-SC>FTA-SC>FTC-SC>FTDW-SM>FTA-SM>FTC-SM. The field test showed that TC-SM with 600 mm spacing produced stable fluctuations with less tillage resistance. The variance analysis and regression equation testing of the experimental results were analyzed to enhance their scientific rigor. The analysis showed that the significances of each factor on the results were in the descending order of shank, space, and tine. The optimal configuration may be with spacing of 600 mm, tine of TC, and shank of SM, which is consistent with the field test and theoretical analysis. Tillage resistance of the DEM simulation was less than that of the field experiment, with an error of less than 10%, due to ignoring the effect of crop roots, straw residue, stones, or blunt tine and shank, which confirms the authenticity of simulation. The effect of spacing on soil disturbance behavior indicates that a mixed soil structure with moderate soil disturbance and soil porosity ratio and a spacing of 600 mm would be a good choice. This study provides an important foundation in selecting spacing for subsoiling to achieve an optimal soil tillage condition. Keywords: subsoiler, space arrangement, mechanism analysis, tillage resistance, soil disturbanceDOI: 10.25165/j.ijabe.20251801.8996Citation: Wang Y M, Lu C J, Fan J J, Zhang X, Chen K, Chen J, et al. Evaluating the effects of subsoiler type and spacing on tillage resistance and soil conservation with DEM simulation and field experiment. Int J Agric & Biol Eng, 2025; 18(1): 115–123.